Warriors & weapons : a young adventurer's guide - Zub, Jim; King, Stacy; Wheeler, Andrew (Graphic novelist) (Dungeons & dragons young adventurer's guide., 2019)
Provides an illustrated guide to the weapons, armor, clothing, and equipment of the tabletop role-playing game "Dungeons & Dragons." Highlights characters, a class flowchart, and tips for putting together an adventuring party.